2010
DOI: 10.1111/j.1365-3083.2010.02438.x
|View full text |Cite
|
Sign up to set email alerts
|

PTPN22 Polymorphism is Related to Autoimmune Disease Risk in Patients with Turner Syndrome

Abstract: Individuals with Turner syndrome (TS) clearly have an increased risk for autoimmune diseases. Recently, an allelic variation (C1858T) of the PTPN22 gene was revealed to be associated with the development of autoimmunity. Thus, the aim of this study was to determine the frequency of the PTPN22 C1858T polymorphism in women with Turner syndrome (TS) compared to controls. Case–control study comprises 142 women with TS (cases) and 180 healthy and fertile women without a history of autoimmune disease (controls). Det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
1
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 28 publications
0
22
1
2
Order By: Relevance
“…Increased CRP [26,21]and GAD antibodies has been found before and the latter has been linked to the presence of isochromosome Xq[27]. Likewise, it is well known that the rate of autoimmunity in general is hugely increased in TS [28] being most pronounced for females with isochromosome Xq [28], and possibly also affected by the presence of allelic variation of the other genes on other chromosomes, such as PTPN22 gene [29]. …”
Section: Discussionmentioning
confidence: 99%
“…Increased CRP [26,21]and GAD antibodies has been found before and the latter has been linked to the presence of isochromosome Xq[27]. Likewise, it is well known that the rate of autoimmunity in general is hugely increased in TS [28] being most pronounced for females with isochromosome Xq [28], and possibly also affected by the presence of allelic variation of the other genes on other chromosomes, such as PTPN22 gene [29]. …”
Section: Discussionmentioning
confidence: 99%
“…No differences in the percentage of regulatory T cells have been found between girls with Turner syndrome and controls, although girls with Turner syndrome who already had autoimmune disease had a significantly lower regulatory T cell percentage (Gawlik et al, ). PTPN22, ZFAT and MYO9B polymorphisms have been studied in pediatric and adult individuals with Turner syndrome in diverse populations (Bianco et al, ; Villanueva‐Ortega et al, ). Although these areas of study help to enhance our knowledge and understanding of the possible mechanisms behind the increased risk of autoimmune disease in Turner syndrome, there is currently no clinical utility in testing for these cytokine, T cell, or genetic abnormalities.…”
Section: Autoimmune Disordersmentioning
confidence: 99%
“…35,36 Bone mineral density TS patients have low bone mineral density (BMD), but it can be maintained at normal levels if the patient follows a healthy lifestyle with regular practice of physical exercise, early introduction of an appropriate dose of estrogens (hormone replacement therapy), as well as calcium and vitamin D. 3,37 The VDR gene binds to the active form of vitamin D to modulate gene transcription. 25,26 The allelic variation of the PTPN22 gene, C1858T, was associated with the risk of autoimmune diseases in Brazilian patients with TS. 38 Vitamin D deficiency is associated with increased risk of fractures, autoimmune diseases, type 1 and 2 diabetes, hypertension and heart disease, 38 clinical characteristics present in patients with TS.…”
Section: Short Staturementioning
confidence: 99%
“…Vitamin D, in turn, is a steroid hormone which regulates bone metabolism, immune response, cell proliferation and differentiation. 26 The study published in 2012 reported that one of its main limitations was the small number of patients with TS and thyroid disorders ---only 22 ---which reduced the statistical power to detect associations between polymorphisms of the VDR gene and autoimmune diseases in TS. 3 Considering the abovementioned facts, the VDR gene was investigated in four studies, one of them associated with growth, 18 two with BMD 22,23 and one with thyroid anomalies.…”
Section: Short Staturementioning
confidence: 99%